1999
DOI: 10.1128/jb.181.2.483-492.1999
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genomics To Identify Bacterial Undecaprenyl Pyrophosphate Synthetase: Cloning, Expression, and Characterization of the Essential uppS Gene

Abstract: The prenyltransferase undecaprenyl pyrophosphate synthetase (di-trans,poly-cis-decaprenylcistransferase; EC2.5.1.31 ) was purified from the soluble fraction of Escherichia coli by TSK-DEAE, ceramic hydroxyapatite, TSK-ether, Superdex 200, and heparin-Actigel chromatography. The protein was labeled with the photolabile analogue of the farnesyl pyrophosphate analogue (E,E)-[1-3H]-(2-diazo-3-trifluoropropionyloxy)geranyl diphos-phate and was detected on a sodium dodecyl sulfate-polyacrylamide gel as a protein wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
103
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(107 citation statements)
references
References 41 publications
(33 reference statements)
3
103
1
Order By: Relevance
“…3). Trace amounts of nona-, deca-, and dodeca-prenyl alcohol derivatives were always detected together with the predominant C 55 -P lipid in membrane extracts, confirming the high but not absolute specificity of the corresponding UppS synthase activities observed during in vitro assays (Thorne & Kodicek, 1966;Higashi et al, 1967Higashi et al, , 1970bScher et al, 1968;Gough et al, 1970;Umbreit et al, 1972;Umbreit & Strominger, 1972b;Apfel et al, 1999).…”
Section: Biosynthesis and Recycling Of Undecaprenyl Pyrophosphatementioning
confidence: 59%
See 3 more Smart Citations
“…3). Trace amounts of nona-, deca-, and dodeca-prenyl alcohol derivatives were always detected together with the predominant C 55 -P lipid in membrane extracts, confirming the high but not absolute specificity of the corresponding UppS synthase activities observed during in vitro assays (Thorne & Kodicek, 1966;Higashi et al, 1967Higashi et al, , 1970bScher et al, 1968;Gough et al, 1970;Umbreit et al, 1972;Umbreit & Strominger, 1972b;Apfel et al, 1999).…”
Section: Biosynthesis and Recycling Of Undecaprenyl Pyrophosphatementioning
confidence: 59%
“…The first uppS gene was identified much more recently, in 1998 by Ogura's group, using a genomic DNA library of M. luteus B-P 26 constructed in E. coli and a screening of recombinant clones for overexpression of the synthase activity (Shimizu et al, 1998). Orthologs were subsequently identified in various Gram-positive and Gram-negative bacterial species (Apfel et al, 1999) and this gene was demonstrated to be essential in E. coli (Kato et al, 1999) and Streptococcus pneumoniae (Apfel et al, 1999). Interestingly, these newly identified proteins did not exhibit significant sequence similarity with members of the trans-prenyltransferase family and in particular they did not carry the characteristic aspartate-rich DDXXD motif that is involved in substrate binding via a Mg 21 bridge in the latter enzyme family (Chen et al, 1994).…”
Section: Biosynthesis and Recycling Of Undecaprenyl Pyrophosphatementioning
confidence: 99%
See 2 more Smart Citations
“…showed that not only the primary but also the threedimensional structure of cis-prenyltransferase were totally different from those of trans-prenyltransferases [3][4][5]. Homologous genes for cis-prenyltransferases have been identified in various organisms [6][7][8][9][10][11][12][13], revealing five highly conserved regions in the primary structure of all cis-prenyltransferases [3]. On the other hand, cis-prenyltransferases are classified into three subfamilies with respect to product chain length, i.e.…”
mentioning
confidence: 99%